Photonic curing of silver paths on 3D printed polymer substrate. Issue 1 (4th February 2019) - Krzeminski, Jakub; Blicharz, Bartosz; Skalski, Andrzej; Wroblewski, Grzegorz; Jakubowska, Małgorzata; Sloma, Marcin
Abstract : Purpose: Despite almost limitless possibilities of rapid prototyping, the idea of 3D printed fully functional electronic device still has not been fulfilled – the missing point is a highly conductive material suitable for this technique. The purpose of this paper is to present the usage of the photonic curing process for sintering highly conductive paths printed on the polymer substrate. Design/methodology/approach: This paper evaluates two photonic curing processes for the conductive network formulation during the additive manufacturing process. Along with the xenon flash sintering for aerosol jet-printed paths, this paper examines rapid infrared sintering for thick-film and direct write techniques. Findings: This paper proves that the combination of fused deposition modeling, aerosol jet printing or paste deposition, along with photonic sintering, is suitable to obtain elements with low resistivity of 3, 75·10 −8 Ωm. Presented outcomes suggest the solution for fabrication of the structural electronics systems for daily-use applications. Originality/value: The combination of fused deposition modelling (FDM) and aerosol jet printing or paste deposition used with photonic sintering process can fill the missing point for highly conductive materials for structural electronics.